Demographic differences in perceived effectiveness for policies to prevent school shootings: results from a representative survey in New Jersey - Michael Anestis; Jayna Moceri-Brooks; Allison Bond; Daniel Semenza (BMC, 2024)
Abstract Objective To determine what firearm policies New Jersey residents believe will prevent school shootings and the extent to which this varies by sex, firearm ownership status, and political affiliation. Methods A representative sample of New Jersey residents (N = 1,018) was collected via the Eagleton Center on Public Interest Polling (ECPIP). Data were weighted to reflect the state's population. Participants were asked to rate how helpful they perceived different firearm-related policies to be for preventing school shootings. Results Findings indicate that participants perceived universal and expanded background checks, increased mental health funding, and requiring a license for firearm purchases as most effective for preventing school shootings. Arming school personnel, prayer in schools, decreasing the number of entrances at schools, and secure storage requirements were viewed as less effective. Firearm ownership, sex, and political affiliation significantly influenced perceptions of the effectiveness of these policies. Conclusion The study examined the perceived effectiveness of policies to prevent school shootings. The study highlights disparities and commonalities in policy support among different groups, emphasizing the importance of collective efforts to address gun violence in schools.